Threats of zoonotic pathogens in food chain: Current status and gaps in IndiaKey public health Message: - Madhuchhanda Das; Anup Kumar Ojha; Venencia Albert; Saradi Borah; Thandavarayan Ramamurthy; Samaresh Das; Tapan Kumar Dutta; Hosterson Kylla; Rajkumari Mandakini; Sarangthem Indira Devi (Heliyon)
Background: Public health is seriously threatened by transmission of zoonotic infection through the food chain. Factors like increasing population, deforestation, high demand for animal protein, and trade of sub-clinically infected animals are the main causes of the spread of infections from asymptomatic animals to humans. Despite several national programs like Swatch Bharat Abhiyan (The Clean India Mission), prevention of open defecation and water, sanitation, and hygiene (WASH), the incidence of diarrhoeal diseases remains high in India. There is an urgent need to understand the route of the spread of zoonotic infections so that related preventive action can be taken to protect the health of the people. Objective: The purpose of this review is to overview the current threats of zoonotic food-borne infections to humans, challenges, and propose possible solutions to improve the public health system. Methods: Published literatures on ‘foodborne and zoonotic infections’, ‘foodborne outbreak’, ‘zoonotic pathogens’, ‘food animals’, ‘AMR’, and ‘one health’ were reviewed in depth. Strengths, weaknesses, opportunities, and threats analysis (SWOT) was used to assess the problem's depth and find possible solutions. Result: SWOT analysis showed that different national and international programs supporting One Health initiative are the strengths, whereas poor awareness related to animal health issues, insufficient number of veterinary hospitals and excellence centers for diagnosis, and research are the weaknesses. International and National funding opportunities, and policy support for one health initiative remains a long-term vision. The other factors such as cross-boundary food animal trades, a huge number of undiagnosed cases of sub-clinically infected food animals and unreported outbreaks are the potential threats that need timely action through well-designed surveillance and monitoring. Conclusion: The importance of the transmission of zoonotic infection to humans and its impact has probably been understood by the world during the COVID-19 pandemic. Increased human-animal interface, cross-species transmission of a few emerging pathogens, and dissemination of antimicrobial-resistant genes are major concerns. Integrated laboratory surveillance, and one health amalgamation of medical, agriculture, and veterinary health research sectors are crucial to addressing this neglected public health problem.